Classification of Small and Medium Industry (SMI) in Malang Regency Using K-Means based Clustering Method - Sunday Noya; Novenda Kartika Putrianto; Weshley Valentino Salendu (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2021)
Information in the form of a structured database becomes an inevitable requirement in the management and development of an organization. In Malang Regency, there are thousands of Small and Medium Industries (SMIs) that have not been completely recorded. This makes it difficult for stakeholders to find out the profile and potential of SMIs, especially SMIs that require special attention. This study aims to classify SMIs in Malang Regency by utilizing the K-means clustering method, using 5 clustering variables: the type of business, investment value, business age, product variations, and average monthly income. The data used in this study is primary data which consist of the five variables of the 183 SMIs sample located in Malang Regency. The result is that the SMIs are classified into 3 clusters, and patterned based on investment value, business age, and average monthly income. Nearly 90% of SMIs are grouped into clusters with the lowest specifications which provide an overview of the current condition of SMIs in Malang Regency.